Green Synthesis of Gold Nanoparticles using Aqueous Garlic (Allium sativum L.) Extract, and Its Interaction Study with Melamine - Yoki Yulizar; Harits Atika Ariyanta; Lingga Abduracman (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Gold nanoparticles (AuNPs) have been successfully prepared by green synthesis method using aqueous extract of garlic with the Latin name of Allium sativum L. (ASL) as a reducing and stabilizing agents. Identification of active compounds in aqueous ASL extract was conducted by phytochemical analysis and Fourier transform infrared (FTIR) spectroscopy, while the synthesized AuNPs were characterized using UV-Vis spectrophotometer and transmission electron microscopy-selected area electron diffraction (TEM-SAED). The AuNPs formation was optimized at aqueous ASL extract concentration of 0.05%, HAuCl4 concentration of 2.0×10-4 M, and pH of 3.6. The optimized AuNPs was characterized   using TEM, and has a spherical shape with particle size of 15±3 nm. The particles were also stable up until one month. The synthesized AuNPs has been studied its interaction with melamine, and showed the optimum pH of interaction at 3.6.